A novel KCNC3 gene variant in the voltage-dependent Kv3.3 channel in an atypical form of SCA13 with dominant central vertigo - Bernhard, Felix P.; Schütte, Sven; Heidenblut, Moritz; Oehme, Moritz; Rinné, Susanne; Decher, Niels (Frontiers in Cellular Neuroscience, 2024)
Potassium channel mutations play an important role in neurological diseases, such as spinocerebellar ataxia (SCA). SCA is a heterogeneous autosomal-dominant neurodegenerative disorder with multiple sub-entities, such as SCA13, which is characterized by mutations in the voltage-gated potassium channel Kv3.3 (KCNC3). In this study, we present a rare and atypical case of SCA13 with a predominant episodic central rotational vertigo, while the patient suffered only from mild progressive cerebellar symptoms, such as dysarthria, ataxia of gait and stand, and recently a cognitive impairment. In this patient, we identified a heterozygous variant in KCNC3 (c.2023G>A, p.Glu675Lys) by nextgeneration sequencing. This Kv3.3 E675K variant was studied using voltage-clamp recordings in Xenopus oocytes. While typical SCA13 variants are dominant-negative, show shifts in the voltage-dependence of activation or an altered TBK1 regulation, the Kv3.3 E675K variant caused only a reduction in current amplitude and a more pronounced cumulative inactivation. Thus, the differences to phenotypes observed in patients with classical SCA13 mutations may be related to the mechanism of the observed Kv3.3 loss-of-function. Treatment of our patient with riluzole, a drug that is known to also activate potassium channels, turned out to be partly beneficial. Strikingly, we found that the Kv3.3 and Kv3.3 E675K inactivation and the frequency-dependent cumulative inactivation of the Kv3.3 E675K variant was antagonized by increased extracellular potassium levels. Thus, and most importantly, carefully elevated plasma potassium levels in the physiological range, or novel drugs attenuating Kv3.3 inactivation might provide novel therapeutic approaches to rescue potassium currents of SCA13 variants per se. In addition, our findings broaden the phenotypic spectrum of Kv3.3 variants, expanding it to atypical phenotypes of Kv3.3-associated neurological disorders.